New data on the species diversity and ecology of Myxomycetes in Mezhynsky National Nature Park (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Difference in the species diversity of myxomycetes collected at the territories of Mezynsky National Nature Park by Professor I. G. Borshchov in 1868 and by the authors in 2008 are discussed. Only 9 species were found to be common for list of Borshchov’s collections and list of collections made in 2008: Arcyriacinerea (Bull.) Pers., Comatrichanigra (Pers. ex J.F.Gmel.) J.Schrцt.,Didymiummelanospermum (Pers.) T. Macbr., Fuligoseptica (L.) F.H.Wigg., Hemitrichiaclavata(Pers.) Rostaf., Lycogala epidendrum (L.) Fr., Stemonitis fuscaRoth, Trichia varia (Pers. ex J.F.Gmel.) Pers. and Tubulifera arachnoideaJacq.It was not succeeded to find 7 slime molds species which were revealed by Professor I.G. Borshchov in 1868: Amaurochaeteatra(Alb. & Schwein.) Rostaf.,Arcyriadenudata(L.) Wettst., Brefeldia maxima(Fr.) Rostaf., in Fuckel, Jahrb., Leocarpusfragilis(Dicks.) Rostaf., Physarum psittacinumDitmar, Trichia decipiens(Pers.) T. Macbr. andTrichia favoginea(Batsch) Pers. but 13 previously unknown for park territory species were collected in 2008 field season: ArcyriaferrugineaSaut., A.incarnata(Pers. exJ.F. Gmel.) Pers., A. stipata (Schwein.) Lister, Badhamiamacrocarpa (Ces.) Rostaf., Ceratiomyxa fruticulosa(O.F. Müll.) T.Macbr., Cribraria tenellaSchrad., Diachea leucopodia (Bull.) Rostaf., Didymium squamulosum (Alb. & Schwein.) Fr., Metatrichia vesparia (Batsch) Nann.-Bremek. exG.W.Martin& Alexop., Physarum album (Bull.) Chevall., Ph. leucopusLink, Reticularia lycoperdon Bull. and Stemonitopsis typhina(F.H. Wigg.) Nann-Bremek. Some aspects of myxomycetous ecological peculiarities,namely substrate adaptation, are considered.
Keywords: myxomycetes, species diversity, substratepreferences, Mezynsky National Nature Park.